Feasibility Test of “Auxora” Ready-To-Wear Clothing with Weaving Techniques - Aqilah Putri Hardianti; Irmayanti Irmayanti (Universitas Negeri Semarang, 2026)
The rapid development of the fashion industry encourages various design innovations in ready-to-wear products. One innovation that can be applied is the use of weaving techniques as an aesthetic element that enhances visual value while incorporating cultural identity into fashion products. This study aimed to develop and determine the feasibility of the